A Simulation Modeling Framework to Optimize Programs Using Financial Incentives to Motivate Health Behavior Change. (January 2016) - Basu, Sanjay; Kiernan, Michaela
Introduction. While increasingly popular among mid- to large-size employers, using financial incentives to induce health behavior change among employees has been controversial, in part due to poor quality and generalizability of studies to date. Thus, fundamental questions have been left unanswered: To generate positive economic returns on investment, what level of incentive should be offered for any given type of incentive program and among which employees?Methods. We constructed a novel modeling framework that systematically identifies how to optimize marginal return on investment from programs incentivizing behavior change by integrating commonly collected data on health behaviors and associated costs. We integrated "demand curves" capturing individual differences in response to any given incentive with employee demographic and risk factor data. We also estimated the degree of self-selection that could be tolerated: that is, the maximum percentage of already-healthy employees who could enroll in a wellness program while still maintaining positive absolute return on investment. In a demonstration analysis, the modeling framework was applied to data from 3000 worksite physical activity programs across the nation.Results. For physical activity programs, the incentive levels that would optimize marginal return on investment ($367/employee/year) were higher than average incentive levels currently offered ($143/employee/year). Yet a high degree of self-selection could undermine the economic benefits of the program; if more than 17% of participants came from the top 10% of the physical activity distribution, the cost of the program would be expected to always be greater than its benefits.Discussion. Our generalizable framework integrates individual differences in behavior and risk to systematically estimate the incentive level that optimizes marginal return on investment.